Determinants of Asean-6 Economic Growth 2013 2023 Period - Simbolon, Chelsea Paulin; Girindra Mega Paksi (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI), Labor Force Participation Rate (LFPR), Research and Development (R&D), and Trade Openness (TO) on economic growth in six ASEAN countries (Indonesia, Malaysia, Thailand, Singapore, the Philippines, and Vietnam) during the period 2013–2023. The research is motivated by the variation in economic growth among ASEAN-6 countries despite their significant contribution to the region’s total GDP. The study employs a quantitative approach using panel data analysis with the Fixed Effect Model (FEM) as the best-fitted model, determined through the Chow test and the Hausman test. Classical assumption tests and robust standard errors are applied to address potential heteroskedasticity. The findings reveal that LFPR and TO have a positive and significant impact on economic growth, while FDI and R&D show no significant effect. Simultaneously, all four independent variables significantly influence economic growth in ASEAN-6. These results indicate that the region’s economic growth is more strongly supported by labor force participation and trade openness rather than foreign direct investment or research and development. This study suggests that ASEAN-6 countries should improve labor quality and strengthen trade openness while implementing structural reforms to maximize the benefits of FDI and enhance investments in R&D.